The Influence of Job Characteristic on Innovative Work Behavior With Work Engagement and Job Stress Being Mediating Variable (Study on Medical Personnel at Puskesmas Kota Pontianak) - Are, MUHAMMAD KHODRI B31111188 (Jurnal Manajemen Update, 2018)
AbstractThis study aims to measure the innovative work behavior of midwives and nurses at Puskesmas Kota Pontianak by using job characteristic as independent variables and work engagement and job stress as mediating variables. Data collection using questionnaires distributed to 100 respondents with 80 questionnaires back, using census sampling technique and Likert scale used for data measurement. The classical assumption test and path analysis were used to process the data using the IBM SPSS v22 application. The results of this study indicate that job characteristics have positive and significant effect on the innovative work behavior, work engagement and job stress, while work involvement is positively and significantly related to the nature of innovative work, but job stress has no significant effect on the innovative work behavior.Keywords: Job Characteristics, Work Engagement, Job Stress, Innovative Work Behavior, Puskesmas Kota Pontianak